Smart Technologies Lead to Smart Answers? On the Claim of Smart Sensing Technologies to Tackle Animal Related Societal Concerns in Europe Over Current Pig Husbandry Systems - Giersberg, Mona F. (Front Vet Sci, 2021)
Current pig production systems in Europe are subject to public criticism. At the same time, Precision Livestock Farming (PLF) technologies, which allow for automated animal monitoring are entering commercial pig farms. With their claim of improving animal health and welfare, these innovations may respond to public concerns. However, they may raise problems of societal acceptance themselves. In this review, we investigate whether the available literature allows for an analysis to which extent PLF can mitigate or reinforce societal concerns related to pig production. We first analyze papers on pig husbandry systems in general, and then those on PLF as an innovation in animal production. In general, there is a tension between citizens and farmers. Citizens hold rather negative attitudes whereas farmers evaluate pig production more positively. Literature on attitudes of other actors, such as veterinarians, is missing. Information on the attitudes toward PLF of stakeholders other than farmers is lacking. Possible challenges of societal acceptance of PLF and chances to overcome these are only discussed in theoretical approaches. We conclude that to analyze the role of PLF in addressing societal concerns over pig production, there is a need for further empirical research including attention to underlying values of all stakeholders. This should focus on the attitudes of the currently missing stakeholders toward pig husbandry in general, and on those of the wider society toward PLF. Only by means of additional data, it will be possible to evaluate whether PLF has the potential to address societal concerns related to pig production.